PENGARUH KONSEP DIRI AKADEMIK, MINAT AKADEMIK, HARAPAN AKADEMIK ORANG TUA DAN DUKUNGAN SOSIAL TERHADAP KECEMASAN AKADEMIK PADA MAHASISWA PENDIDIKAN EKONOMI - Talisya Alvini; Mardi Mardi; Rida Prihatni (Yayasan Education and Social Center, 2023)
Academic anxiety is a feeling triggered by a lack of confidence in one's ability to cope with academic tasks. Students have different backgrounds in lectures, leading to academic anxiety. To achieve their academic degree, undergraduate students must complete their final assignments properly. For students, the final assignment or thesis can cause anxiety because internal and external factors influence it. Using a quantitative approach to the survey method. This research aims to determine the effect of academic self-concept, academic interest, parents' academic expectations, and social support on academic anxiety in 2019 Economics Education students. The population in this study was students of the economics education study program, faculty of economics, Jakarta State University. One hundred eleven students and a total sample of 87 respondents. The sampling technique used proportional stratified random sampling with a significance level of 5%. The results of partial hypothesis testing show that the academic self-concept variable has a negative and significant effect on academic anxiety as evidenced by the tcount < ttable (-3.101 <1.66298), the academic interest variable has a negative and significant effect on academic anxiety is proven by the value of tcount < ttable (-2.339 < 1.66298), the variable of parents' academic expectations has a positive and significant effect on academic anxiety as evidenced by the value of tcount < ttable (0.690 < 1.66298 ), social support variable has a negative and significant effect on academic anxiety as evidenced by the value of tcount < ttable (-3.322 <1.66298) and simultaneous hypothesis testing shows that academic self-concept, academic interest, parents' academic expectations, and social support simultaneously influence academic anxiety as evidenced by the value of Fcount > Ftable (5.782 > 2.48). Based on the results of the study shows that there is a negative and significant influence between academic self-concept on academic anxiety. There is a negative and significant influence between academic interest and academic anxiety. The positive and significant influence between parents' academic expectations on academic anxiety. There is a negative and significant effect of social support on academic anxiety. And there is a simultaneous influence between academic self-concept, academic interest, parents' academic expectations, and social support on academic anxiety